Research Agenda Setting for the Argentinean Chaco : Biofuels, cattle breeding and sustainable development in the Chaco of Argentina = Construyendo una agenda conjunta para la investigación en el Chaco Argentino : biocombustibles, ganadero y desarrollo sostenible en el Chaco Argentina - Nijhof, B.S.J.; Prieto Garra, Daniel; Bindraban, P.S.; Mansfeld, M.J.M. van; Jongman, R.H.G.; Querner, E.P. (Alterra, Wageningen, 2020)
This report is the result of a project carried out on request of the Dutch Embassy in Buenos Aires for identification of the potential developments of agricultural developments and its environmental and land use implications in the Argentinean Chaco. A joint Argentinean Dutch workshop has been held in Santiago del Estero with invited guests from various Argentinean interest groups. The workshop had the form of a SWOT analysis. The results are presented in this report.